2022
DOI: 10.3390/metabo12010067
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Fructose as a Cardiovascular Risk Factor: An Update

Abstract: There is increasing presence of fructose in food and drinks, and some evidence suggests that its higher consumption increases cardiovascular risk, although the mechanisms still remain not fully elucidated. Cardiovascular diseases (CVD) are still responsible for one-third of deaths worldwide, and therefore, their prevention should be assessed and managed comprehensively and not by the evaluation of individual risk factor components. Lifestyle risk factors for CVD include low degree of physical activity, high bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Eating habits have a great impact on TG metabolism. Higher intake of simple sugars was found to contribute to increased plasma concentrations of TG [ 39 ]. A recent analysis of 191,558 participants revealed that higher fish consumption was associated with lower TG levels [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eating habits have a great impact on TG metabolism. Higher intake of simple sugars was found to contribute to increased plasma concentrations of TG [ 39 ]. A recent analysis of 191,558 participants revealed that higher fish consumption was associated with lower TG levels [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Low WG intake is probably one of the most important but easiest-to-be-ignored factors. With the literature review, we found more and more researchers have noticed the impact of WGs on CVD and the association between CVD and WG intake [ 13 , 20 , 21 , 22 , 23 , 24 , 25 ]. However, few studies have focused on a comprehensive analysis of the long-term trend of CVD mortality attributable to low WG intake in China.…”
Section: Discussionmentioning
confidence: 99%
“…A newly published prospective study based on a long-running birth cohort study in Australia also concluded the same result [ 22 ]. Active ingredients in whole grains, such as dietary fiber, vitamins, minerals, antioxidants, lingams, phytosterols, etc., can affect cardiovascular health through the metabolism of sugar, blood lipids, lipoproteins, and vascular endothelial function [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that tooth decay is directly related to the development of periodontal disease, both being linked to poor nutritional support for the patient [ 2 ]. Individuals suffering from periodontal disease are at high risk of developing severe cardiovascular events [ 3 ], heart attack, and stroke, which are responsible for a high mortality rate or health complications affecting the quality of life [ 4 , 5 ]. Furthermore, periodontal disease, characterized by chronic inflammatory events, was closely studied due to an additional risk of developing oral cancer in relation to habits such as smoking or alcohol intake [ 6 ].…”
Section: Introductionmentioning
confidence: 99%